Complexity and hybrid effects in the delivery and evaluation of youth programmes in a remote Indigenous community. Issue 1 (6th February 2019) - Staines, Zoe; Moran, Mark
Abstract: Indigenous Australians continue to experience entrenched disadvantage. Despite billions being spent, 'Closing the Gap' indicators remain resistant to change. It has become increasingly apparent that progress has been hindered by persistent administration and implementation issues in Indigenous Affairs, especially with the funding modalities deployed. This study uses the remote Queensland Indigenous community of Aurukun as a case study to examine the effectiveness and evaluation problems arising from overlapping programmes delivered to Aurukun children and youth (5–18 years of age). It documents programmatic crowding occurring in Aurukun, which has the potential to place considerable demands on the intended participants, and results in hybridised effects that are not understood. Within this context, robust evaluation – even through the use of sophisticated methods – is near impossible. Abstract : This study uses the remote Queensland Indigenous community of Aurukun as a case study to examine evaluation problems arising from programmatic crowding. It documents the crowding of programmes in Aurukun, which has the potential to place considerable demands on intended participants, and creates hybridised effects that are not understood.